Public sector accountants’ opinion on impact of a new enterprise system - Zainol, Zaini; mohd farid fernandez, dahlia fernandez; Ahmad @ Abdul Mutalib, Hawa (Elsevier, 2017)
In digital era, citizen has higher expectation on public sector services. Excellence services and delivery system are expected from them. Towards this, the need to have a good system such as Enterprise Resource Planning (ERP) system as evidence in private sector is one of the crucial efforts. Prior researches especially in private sectors have recorded various benefits of implementing ERP systems among others, fast data processing, higher integration, up to date information, higher staff satisfaction, better governance and transparency and reduce operating cost. This study focused on the impact of ERP via ePBT system in the local agencies (LAs) of Malaysia. ePBT was developed to improve the delivery of LAs via the usage of information, communication and technology (ICT). It has been implemented by Malaysian Administrative Modernisation and Management Planning Unit (MAMPU) and Local Government Department (LGD), at various stages. This study used a questionnaire survey distributed to LAs’ organization in Peninsular Malaysia that are currently utilizing the ePBT system, and drew a total response of 52.53 percent. The impact of this system was analyzed based on opinions received by LAs’ accountants, who are mostly the main user of this system. There four dimensions of ePBT impacts which are based on DeLone and McLean IS success model (system and information quality) and the BSC measurement model (internal business and innovation & learning perspectives). This study provides a better understanding regarding the impact of ERP implementation in the context of LAs in Malaysian public sector.